JOHANN WOLFGANG VON GOETHE: A LIFE OF CREATIVITY, WISDOM, AND INSPIRATION. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Johann Wolfgang von Goethe (1749-1832) was a German writer, poet, scientist, and statesman whose vast body of work left an indelible mark on literature and philosophy. Known for his literary masterpieces such as *Faust*, *The Sorrows of Young Werther*, and his scientific inquiries into natural phenomena, Goethe was a polymath whose life was a testament to intellectual and creative exploration. This article delves into Goethe's life, his philosophical outlook, and the inspiring words that continue to resonate with generations.